2000
DOI: 10.1021/jm000269t
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of a Series of Pyrrolo[3,2-d]pyrimidine Derivatives and Related Compounds as Neuropeptide Y5 Receptor Antagonists

Abstract: Neuropeptide Y (NPY) has been shown to play an important role in the regulation of food intake and energy balance. Pharmacological data suggests that the Y5 receptor subtype contributes to the effects of NPY on appetite, and therefore a Y5 antagonist might be a useful therapeutic agent for the treatment of obesity. In attempts to identify potential Y5 antagonists, a series of pyrrolo[3, 2-d]pyrimidine derivatives was prepared and evaluated for their ability to bind to Y5 receptors in vitro. We report here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 45 publications
2
63
0
Order By: Relevance
“…NVP was kindly supplied by Boehringer-Ingelheim GmbH. 12-OH-NVP (Grozinger et al, 1995), 12-Cl-NVP (Kelly et al, 1995), and 4-Cl-NVP (Hargrave et al, 1991;Norman et al, 2000) were synthesized as described previously. Phosphate-buffered saline (pH 7.4, fetal bovine serum (FBS), 1640 RPMI-HEPES modified, Eagle's minimal essential medium nonessential amino acids solution, and penicillin-streptomycin liquid were purchased from Invitrogen Canada, Inc. (Burlington, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…NVP was kindly supplied by Boehringer-Ingelheim GmbH. 12-OH-NVP (Grozinger et al, 1995), 12-Cl-NVP (Kelly et al, 1995), and 4-Cl-NVP (Hargrave et al, 1991;Norman et al, 2000) were synthesized as described previously. Phosphate-buffered saline (pH 7.4, fetal bovine serum (FBS), 1640 RPMI-HEPES modified, Eagle's minimal essential medium nonessential amino acids solution, and penicillin-streptomycin liquid were purchased from Invitrogen Canada, Inc. (Burlington, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…In short, reaction of pyridine 1 with a mixture of phosphoryl chloride and phosphorous pentachloride rendered the known 2 [11] in high yield. Displacement of the chloro group of 2 with a methoxy group, using sodium methoxide in methanol finished intermediate 3 which was in turn transformed to the desired 4 by the action of treatment with a base followed by condensation of the resultant carbanion with diethyl oxalate.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting solution was allowed to react, with stirring, for 20 at 0°C and then allowed to warm to room temperature and stirred for an additional one hour. The resulting slurry was filtered and the solids collected by vacuum filtration to afford the title compound 6-Chloro-2-methyl-3-nitropyridine 2 as a brown solid solid [11].…”
Section: Experimental Workmentioning
confidence: 99%
“…Two original methods of preparing 6-substituted pyrrolo[3,2-d]pyrimidines 27 are described in [31]. The authors showed that 4-chloro-5-nitropyrimidines 23 could act as arylating agents toward enamines.…”
Section: Abmentioning
confidence: 99%